Contacts between the Islamic world and Northern Europe in the pre-Mongol period - Jankowiak, M (Oxford University Press, 2020)
Northern Europe and the Islamic world, although separated by the wide belt of the steppe, were in contact throughout the pre-Mongol period. The intensity of these contacts varied over time and so did their geography: objects of Islamic provenance were imported to the basin of the Kama in the 7th–10th centuries, to the lands settled by the Scandinavians and those Slavs who were under their political or cultural influence in the 9th and 10th centuries, and to the northern edge of the steppe in the two centuries before the Mongol invasion. This chapter surveys the finds of Islamic objects associated with these interactions—mostly silver coins and silverware—and investigates the mechanisms that account for their importation to the North.